Nota sobre Hoplocama brevis klug, (Hymenoptera tenthredinidae) - Oro, A.=700 1 Artigues, M.; Avilla, J.; Urbina, V.; Sarasua, M.J.
(Es, En)
ilus., 6 ref.
Keywords: HYMENOPTERA; TENTHREDINIDAE; HOPLOCAMPA; RIESGO; ESPAÑA; HOPLOCAMPA BREVIS; FACTORES DE RIESGO